Immunogenicity and safety of a live attenuated varicella vaccine co-administered with inactive hepatitis A vaccine: A phase 4, single-center, randomized, controlled trial. Issue 1 (31st December 2023) - Sun, Dapeng; Yu, Dan; Du, Zhenhua; Jia, Ningning; Liu, Xiaodong; Sun, Jianwen; Xu, Qing; Sun, Zhuoqun; Luan, Chunfang; Lv, Jingjing; Xiong, Ping; Zhang, Li; et al.
ABSTRACT: Co-administration of vaccines can facilitate the introduction of new vaccines in immunization schedules. This study aimed to evaluate the immunogenicity and safety of co-administration with live attenuated varicella vaccine (VarV) and inactivated hepatitis A vaccine (HepA) among children aged 12 ~ 15 months. In this phase 4 clinical trial, 450 children were randomized with a ratio of 1:1 to receive VarV and Hep A simultaneously (Group A) or separately (Group B). The primary endpoints were the seroconversion rate of anti-varicella-zoster virus (VZV) antibodies 42 days after vaccination of VarV and the seroconversion rate of anti-Hepatitis A virus (HAV) antibodies 30 days after two-dose vaccination of HepA. After full immunization, the seroconversion rates of anti-VZV antibodies were 91.79% in Group A and 92.15% in Group B; the geometric mean titers (GMTs) were 11.80 and 12.19, respectively. The seroconversion rates of anti-HAV antibodies were 99.48% in Group A and 100.0% in Group B; the geometric mean concentrations (GMCs) reached 9499.11 and 9528.36 mIU/ml, respectively. The lower limits of the 95% CI for the seroconversion difference of anti-VZV antibodies and anti-HAV antibodies were −5.86% and −2.90%, which greater than the predefined non-inferiority margin (−10%). The incidence rate of adverse reactions in Group A was lower than Group B (9.33% vs 16.22%), and only one serious adverse event was reported in Group B, which was unrelated to the study vaccine. In conclusion, the co-administration of VarV with HepA has non-inferior immunogenicity and safety profiles were quite comparable with the separate administration of both vaccines. Trial registration number : NCT05526820 (ClinicalTrials.gov).